A relação entre as transferências voluntárias do governo do estado do Ceará e a votação para governador - Gurgel, Guilherme Muniz (2019)
The present study investigated the impact of voluntary transfers from government of Ceará by Secretaria das Cidades from 2007 to 2018 in the state elections. Fiscal and political variables, as well as developmental characteristics of the municipalities, were incorporated into econometric linear regression models. The results allowed to infer that there is no evidence that voluntary transfers have an impact votes on state election, which presents itself as a variable of interest. However, if the candidate is running for re-election, the ratio is directly proportional to the number of votes. Features such as development in infrastructure or the fact of the municipality being in the Metropolitan Region of Fortaleza did not affect voting. However, the more developed the social aspect of the municipality, bigger the voting. The findings also suggest that the fact that the mayor belongs to the governor’s coalition had a positive influence on the vote. Tests with different specifications were carried out regarding the infrastructure and social variables, where the conclusions drawn from the main model were confirmed.